Ports as A Supporting Factor of Economic Development in Central Kalimantan Province - Siang. I. Suluh (The Institute of Academic Research and Publication (IARP), 2022)
This study aims to determine partially and simultaneously the effect of export value seen from several loading ports on economic growth in the province of Central Kalimantan. This method is explanatory research to test the hypothesis between the hypothesized variables. This study uses secondary data, namely: Export Value through the Port of Kumai, Sampit, Pulang Pisau, and Pangkalan Bun, and Economic Growth in Central Kalimantan Province during 2007-2021. The results of the Multiple Linear Regression analysis of the Semi Logarithma Model partially show that the Export Value through the Port of Loading at the Ports of Kumai and Sampit has a significant and positive influence on Economic Growth in Central Kalimantan Province. In contrast, the Export Value through the Port of Loading Pulang Pisau and Pangkalan Bun has no effect but is positive on Economic Growth in Central Kalimantan Province. However, simultaneously the export value through the loading ports at the ports of Kumai, Sampit, Pulang Pisau, and Pangkalan Bun has a significant influence on economic growth in the province of Central Kalimantan.